1998
DOI: 10.1126/science.282.5394.1711
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish hox Clusters and Vertebrate Genome Evolution

Abstract: HOX genes specify cell fate in the anterior-posterior axis of animal embryos. Invertebrate chordates have one HOX cluster, but mammals have four, suggesting that cluster duplication facilitated the evolution of vertebrate body plans. This report shows that zebrafish have seven hox clusters. Phylogenetic analysis and genetic mapping suggest a chromosome doubling event, probably by whole genome duplication, after the divergence of ray-finned and lobe-finned fishes but before the teleost radiation. Thus, teleosts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
1,172
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,606 publications
(1,251 citation statements)
references
References 33 publications
59
1,172
1
4
Order By: Relevance
“…In accordance with previous reports, phylogenetic analysis in this study clearly revealed three major groups: mammalian MSTNs, avian MSTNs, and two copies of fish MSTNs (MSTN-1/2), respectively. These results confirm that there is an early genome duplication event prior to the teleost radiation but after the divergence of ray-and lobe-finned fishes [24,25]. The clades MSTN-1a, MSTN-1b, MSTN-2a and MSTN-2b appeared in some fish showed that the additional duplication had occurred more recently than the MSTN-1/2 duplication.…”
Section: Discussionsupporting
confidence: 76%
“…In accordance with previous reports, phylogenetic analysis in this study clearly revealed three major groups: mammalian MSTNs, avian MSTNs, and two copies of fish MSTNs (MSTN-1/2), respectively. These results confirm that there is an early genome duplication event prior to the teleost radiation but after the divergence of ray-and lobe-finned fishes [24,25]. The clades MSTN-1a, MSTN-1b, MSTN-2a and MSTN-2b appeared in some fish showed that the additional duplication had occurred more recently than the MSTN-1/2 duplication.…”
Section: Discussionsupporting
confidence: 76%
“…The number and identity of genes in the most recent common ancestor of bony fish is based on the maximal parsimony reconstruction in [1]. For instance, the ancestor of bony fish has 11 paralog group members in HoxA while zebrafish HoxAa and HoxAb only have a total of 9 paralog groups represented.…”
Section: A Model For the Amount Of Structural Loss Of Pfcsmentioning
confidence: 99%
“…Most notably there is a tendency for gene loss after duplication [1] which can have a direct, "structural" rather than functional, influence on the retention of PFCs. To assess whether the loss of sequence conservation can be explained in its entirety by gene loss we propose a simple probabilistic model for the rate of PFC loss due to gene loss and stochastic resolution of genetic redundancy (structural causes).…”
Section: Introductionmentioning
confidence: 99%
“…These three families are characterized by numerous paralog miRNA genes at dispersed genomic locations and an additional expansion of families in teleosts. This points at a close association of the miRNA expansion with the genome duplications at the root of vertebrate tree [ 261,99] and early in the evolution of the actinopterygian lineage [8].…”
Section: Micrornasmentioning
confidence: 97%
“…In the case of E2 they separated before the advent of the tetrapods; the split between the two E3 groups predates the last common ancestor of the eutherian mammals. The six copies of E3 in the zebrafish apparently arose after the teleost-specific genome duplication [8].…”
Section: Small Nucleolar Rnas (Snornas)mentioning
confidence: 99%